Penguatan Literasi Numerasi Matematis Siswa Kelas XII SMAN 1 Kadugede Kuningan melalui Program Pengabdian Berbasis Kurikulum Merdeka - Adiastuty, Nuranita; Taufik, Azin; Riyadi, Mohamad (Yayasan Dekhalisha Global Prestise, 2026)
The mathematical literacy competency of Indonesian students remains relatively low based on PISA outcomes, attributable to the limited application of mathematical concepts in everyday life and instructional methods that insufficiently promote critical thinking. The Merdeka Curriculum mandates the strengthening of numeracy literacy through context-based learning and problem-solving approaches. Studies by Putri et al. and Kandaga et al. demonstrate that contextual learning and brain-based learning are effective in enhancing students' mathematical literacy. This community service initiative aimed to improve the mathematical numeracy literacy of 32 Grade XII students at SMAN 1 Kadugede, Kuningan. The implementation methodology comprised: (1) mapping of students' prior knowledge and development of pretest-posttest instruments, (2) teacher training on numeracy literacy-based instructional strategies, (3) implementation of contextual learning and collaborative group discussions, and (4) evaluation employing paired sample t-tests and N-Gain analysis. The findings revealed a statistically significant improvement in mean scores from 46.66 (pretest) to 62.72 (posttest), with t = 13.11 and a p-value of 3.49 × 10⁻¹⁴ (p < 0.05). The mean N-Gain value was 0.304 (moderate category), with 17 students classified in the moderate category and 15 students in the low category. Instruction grounded in numeracy literacy indicators and real-life contextual frameworks was demonstrated to be effective in improving students' mathematical literacy, thereby supporting the implementation of the Merdeka Curriculum. Recommendations encompass extending the duration of the intervention, developing a more varied array of Higher-Order Thinking Skills (HOTS) items, and strengthening individualized mentoring to optimize and ensure more equitable learning outcomes.